Standardized fluoroscopy‐based technique to measure intraoperative cup anteversion. Issue 10 (29th March 2017) - Zingg, Matthieu; Boudabbous, Sana; Hannouche, Didier; Montet, Xavier; Boettner, Friedrich
ABSTRACT: Direct anterior approach (DAA) with the patient lying supine has facilitated the use of intraoperative fluoroscopy and allows for standardized positioning of the patient. The current study presents a new technique to measure acetabular component anteversion using intraoperative fluoroscopy. The current paper describes a mathematical formula to calculate true acetabular component anteversion based on the acetabular component abduction angle and the c‐arm tilt angle (CaT). The CaT is determined by tilting the c‐arm until an external pelvic oblique radiograph with the equatorial plane of the acetabular component perpendicular to the fluoroscopy receptor is obtained. CaT is determined by direct reading on the C‐arm device. The technique was validated using a radiopaque synbone model comparing the described technique to computed tomography anteversion measurement. The experiment was repeated 25 times. The difference in anteversion between the two measuring techniques was on average 0.2° (range −3.0–3.1). The linear regression coefficients evaluating the agreement between the experimental and control methods were 0.99 (95%CI 0.88–1.10, p  < 0.001) and 0.33 (95%CI −1.53–2.20, p  = 0.713) for the slope and intercept, respectively. The current study confirms that the described three‐step c‐arm acetabular cup measuring technique can reproducibly and reliably assess acetabular component anteversion in the supine position, as compared to CT‐imaging. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2307–2312, 2017. Abstract : The current study demonstrates a technique that allows to measure total hip arthroplasty cup anteversion angle perioperatively. It takes advantage of properties associated with a particular setup. The fluoroscopy is positioned perpendicular to the patient and is tilted away from the operated side until the equatorial plane lays perpendicular to the plane of the fluoroscopy receptor. The fluoroscopy tilt angle is determined by direct reading on the device and reported in a chart that gives the corresponding anteversion angle.